SMART AQUASCAPES DENGAN KONTROL SUHU, PENGATUR PH, DAN PAKAN OTOMATIS - Rahmadaniar, Ihda; Priana, Arya Prabudi Jaya; Widodo, Bayu; Fadilah, Fikri; Irmansyah, Irmansyah; Alpino, Jimmy Mohamad; Corazon, Marcella; Fajarudin, Muhammad; Arifia, Revanda; Lovely, Vanya Amanda (Elektrika, 2024)
Aquascape as the art of designing and organizing a miniature water garden inside an aquarium has become a desirable hobby for nature lovers and aquatic enthusiasts. Although it offers natural beauty, aquascape requires intensive attention and maintenance to maintain the balance of the aquarium environment. Therefore, the Smart Aquascape concept emerged as an innovative solution by utilizing the integration of the Internet of Things (IoT) to monitor and control the condition of the aquarium environment in real-time through a digital platform that can help facilitate maintenance for aquascape hob-byists and maintain the balance of the aquarium ecosystem. This research aims to design an IoT system to monitor and con-trol water temperature, implement an automatic feeding mechanism, and design an accurate pH regulation system in an aquascape environment by integrating all these features into one connected control platform. Keywords: aquarium, ecosystem, IoT, smart aquascape, water. ABSTRAK Aquascape sebagai seni merancang dan mengatur taman air miniatur di dalam sebuah akuarium telah menjadi hobi yang diminati oleh pecinta alam dan penggemar akuatik. Meskipun menawarkan keindahan alam, aquascape memerlukan perhatian dan pemeliharaan yang intensif untuk menjaga keseimbangan lingkungan akuarium. Oleh karena itu konsep Smart Aquascape muncul sebagai solusi inovatif dengan memanfaatkan integrasi Internet of Things (IoT) untuk memantau dan mengontrol kondisi lingkungan akuarium secara real-time melalui platform digital yang dapat membantu memu-dahkan perawatan bagi para penghobi aquascape dan menjaga keseimbangan ekosistem akuarium. Penelitian ini ber-tujuan untuk merancang sistem IoT untuk memantau dan mengontrol suhu air, mengimplementasikan mekanisme pemberian pakan otomatis, dan merancang sistem pengaturan pH yang akurat dalam lingkungan aquascape dengan mengintegrasi-kan semua fitur tersebut ke dalam satu platform kontrol yang terhubung.